Application of primary health care principles in national community health worker programs in low- and middle-income countries: a scoping review protocol. Issue 1 (28th January 2021) - Perveen, Shagufta; Mahmood, Mohammad Afzal; Lassi, Zohra S.; Perry, Henry B.; Laurence, Caroline
ABSTRACT: Objective: This scoping review aims to map the available literature on the application of primary health care principles as reflected in the implementation of national-level community health worker programs in low- and middle-income countries. Introduction: There is extensive literature on how community health workers have been used to improve the health status of disadvantaged populations, especially in low- and middle-income countries. Established under the primary health care principles, national community health worker programs were expected to adopt and promote these principles to achieve improvements in health outcomes. However, there is limited evidence of the extent to which primary health care principles have been applied in the implementation of national community health worker programs. Inclusion criteria: The concept to be mapped is the application of primary health care principles in the implementation of national community health worker programs in low- and middle-income countries. Quantitative, qualitative, and mixed methods study designs will be included. Only English-language articles published from September 1978 to the present will be included. Study protocols, narrative reviews, systematic and scoping reviews, commentaries, text and opinion papers, viewpoints, editorials, and conference proceedings/abstracts and correspondences will be excluded. The programs operated by non-governmental organizations and articles not involving community health workers will also be excluded. Methods: Key information sources to be searched include MEDLINE, CINAHL, Embase, and Scopus. Two reviewers will independently screen the titles and abstracts against the inclusion criteria. The data charting will include specific details about the concept, context, study methods, and key findings relevant to the review question. Data will be presented in diagrammatic or tabular form accompanied by a narrative summary.